Genetic Evaluation of Black Sea Bream (Acanthopagrus schlegelii) Stock Enhancement in the South China Sea Based on Microsatellite DNA Markers - Xi Wang; Zhuoying Weng; Yang Yang; Sijie Hua; Hanfei Zhang; Zining Meng (Fishes, 2021)
This is the first genetic evaluation of hatchery-based stock enhancement of black sea bream (Acanthopagrus schlegelii) in the South China Sea after a two-year monitoring period. In this study, microsatellite DNA markers were used to calculate the contribution rate and analyze genetic changes before and after stock enhancement. Two out of one hundred and sixty nine individuals from three recaptured populations were assigned to broodstock with a contribution rate of 1.18%, revealing that the hatchery-released juvenile fish could survive in the natural environment and had a positive effect on population replenishment in wild black sea bream abundance. However, we found that the release population had the lowest genetic diversity and significant genetic differentiation from other populations. In addition, genetic diversity detected in the recaptured population was lower than that in the wild population, and their genetic differentiation reached a significant level. Our results suggested that releasing cultured black sea bream juveniles with low genetic quality might be genetically harmful for the maintenance of wild genotypes. Therefore, it is necessary to assess the genetic variation of the hatchery population before implementing a stock enhancement and establish a long-term evaluation for monitoring the genetic effect caused by releasing this fish species.